2005
DOI: 10.1016/j.febslet.2005.09.098
|View full text |Cite
|
Sign up to set email alerts
|

B7‐H1 (CD274) inhibits the development of herpetic stromal keratitis (HSK)

Abstract: The co-signaling molecule B7-H1 (CD274) functions as both a co-inhibitor through programmed death-1 (PD-1) receptor and a co-stimulator via an as-yet-unidentified receptor on T cells. We investigated the physiological role of endogenous B7-H1 in the pathogenesis of herpetic stromal keratitis (HSK) caused by herpes simplex virus type 1 (HSV-1). Following HSV-1 infection of the cornea of mice, B7-H1 expression was up-regulated in the CD11b + macrophage population in the draining lymph nodes (dLN) and in the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
0
38
1
Order By: Relevance
“…The PD-1 pathway is involved in the development of T cell tolerance and has been implicated in the persistence of a variety of chronic viral infections, including lymphocytic choriomeningitis virus, HIV, HBV, and hepatitis C virus (37)(38)(39)(40)(41)(42)(43)(44). There is already some evidence that blockade of the PD-1/programmed death ligand-1 synapse could alter the balance between cytolytic and noncytolytic CD8 + effector T cell functions, resulting in exacerbation of immune-mediated tissue damage in herpetic keratitis or in autoimmune enteritis (45,46). It is possible that the PD-1 pathway acts as a mechanism by which CD8 + T cells engage in cross-talk with the target cells to program their effector functions; the hypothesis that the PD-1 pathway may have a role in modulating the effector functions of virus-specific CD8 + T cells deserves to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The PD-1 pathway is involved in the development of T cell tolerance and has been implicated in the persistence of a variety of chronic viral infections, including lymphocytic choriomeningitis virus, HIV, HBV, and hepatitis C virus (37)(38)(39)(40)(41)(42)(43)(44). There is already some evidence that blockade of the PD-1/programmed death ligand-1 synapse could alter the balance between cytolytic and noncytolytic CD8 + effector T cell functions, resulting in exacerbation of immune-mediated tissue damage in herpetic keratitis or in autoimmune enteritis (45,46). It is possible that the PD-1 pathway acts as a mechanism by which CD8 + T cells engage in cross-talk with the target cells to program their effector functions; the hypothesis that the PD-1 pathway may have a role in modulating the effector functions of virus-specific CD8 + T cells deserves to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several groups have demonstrated that blocking PD-1:PD-Ls interactions in vitro reverses the exhaustion of HIV and hepatitis C virus-specific CD8 ϩ and CD4 ϩ T cells and restores cytokine production and proliferation (36, 38, 56, 57). Moreover, administration of PD-L1-specific blocking mAbs leads to exacerbated keratitis-increased HSV-specific effector CD4 ϩ T cell proliferation, IFN-␥ production, and survival, suggesting that PD-L1 may participate in limiting immune-mediated tissue damage in herpes stromal keratitis infection (58). Besides, during hepatitis B virus infection, PD-1:PD-L1 interactions were shown to contribute to the suppression of IFN-␥ secretion following Ag recognition in the liver (59).…”
Section: Discussionmentioning
confidence: 99%
“…ϩ dendritic cells, in conjunction with increased viral load (23); in another study, monoclonal antibody blockade of PD-L1 resulted in decreased apoptosis and increased proliferation and IFN-␥ secretion by HSV-1-specific CD4 T cells, which exasperated herpetic stromal keratitis (24).…”
Section: Cells and Pd-l1mentioning
confidence: 99%